Comment on Kittichet et al. (doi: 10.1111/odi.14905) - Efsun Somay; Erkan Topkan; Ugur Selek; Berrin Pehlivan (Oral Diseases, 2025)
Objectives To evaluate the association between oral mucosal diseases, oral health-related quality of life (OHRQoL), and depressive symptoms, and to explore differences across categories. Materials and methods In this cross-sectional observational pilot study, consecutive outpatients with oral mucosal disease were enrolled at the Dental Clinic of the Policlinico of Bari over one year. OHRQoL and depressive symptoms were assessed using the Oral Health Impact Profile-14 (OHIP-14) and Patient Health Questionnaire-9 (PHQ-9). Participants were classified into four diagnostic groups: idiopathic/chronic orofacial pain syndromes, autoimmune diseases, oral potentially malignant disorders (OPMDs), and reactive-inflammatory/traumatic lesions. Nonparametric tests and a multivariable negative binomial regression model were applied. Results Sixty-six patients were included, and OHIP-14 and PHQ-9 scores showed a moderate positive correlation (Spearman's p = 0.41; p < 0.01). Kruskal-Wallis testing suggested a difference in OHIP-14 scores across groups (p = 0.03), with the greatest exploratory post hoc difference between chronic orofacial pain syndromes and OPMDs (adjusted p = 0.03), whereas PHQ-9 scores did not differ across groups (p = 0.93). Conclusions Diagnostic category appeared to influence OHRQoL, but not depressive symptoms; however, findings should be considered exploratory. Clinical significance These exploratory findings suggest that OHRQoL assessment may complement oral mucosal disease evaluation.